# Solve for v (v-1)(v+5)=v^2+4v-2

(v-1)(v+5)=v2+4v-2
Simplify (v-1)(v+5).
Expand (v-1)(v+5) using the FOIL Method.
Apply the distributive property.
v(v+5)-1(v+5)=v2+4v-2
Apply the distributive property.
v⋅v+v⋅5-1(v+5)=v2+4v-2
Apply the distributive property.
v⋅v+v⋅5-1v-1⋅5=v2+4v-2
v⋅v+v⋅5-1v-1⋅5=v2+4v-2
Simplify and combine like terms.
Simplify each term.
Multiply v by v.
v2+v⋅5-1v-1⋅5=v2+4v-2
Move 5 to the left of v.
v2+5⋅v-1v-1⋅5=v2+4v-2
Rewrite -1v as -v.
v2+5v-v-1⋅5=v2+4v-2
Multiply -1 by 5.
v2+5v-v-5=v2+4v-2
v2+5v-v-5=v2+4v-2
Subtract v from 5v.
v2+4v-5=v2+4v-2
v2+4v-5=v2+4v-2
v2+4v-5=v2+4v-2
Move all terms containing v to the left side of the equation.
Subtract v2 from both sides of the equation.
v2+4v-5-v2=4v-2
Subtract 4v from both sides of the equation.
v2+4v-5-v2-4v=-2
Combine the opposite terms in v2+4v-5-v2-4v.
Subtract v2 from v2.
4v-5+0-4v=-2
4v-5-4v=-2
Subtract 4v from 4v.
0-5=-2
Subtract 5 from 0.
-5=-2
-5=-2
-5=-2
Since -5≠-2, there are no solutions.
No solution
Solve for v (v-1)(v+5)=v^2+4v-2

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top